Configurational Isomerization-Induced Orientation Switching: Non-Fused Ring Dipodal Phosphonic Acids as Hole-Extraction Layers for Efficient Organic Solar Cells - Zhang, Lei; Wang, Yuxing; Wen, Junjie; Huang, Yifan; Gao, Jiaxin; Duan, Yuxin; Park, Soohyung; Shin, Woojin; Ma, Zaifei; Liu, Miao; Cho, Sang Wan; Park, Yeonju; et al. (John Wiley & Sons Ltd., 2024)
Phosphonic acid (PA) self-assembled molecules have recently emerged as efficient hole-extraction layers (HELs) for organic solar cells (OSCs). However, the structural effects of PAs on their self-assembly behaviors on indium tin oxide (ITO) and thus photovoltaic performance remain obscure. Herein, we present a novel class of PAs, namely "non-fused ring dipodal phosphonic acids" (NFR-DPAs), featuring simple and malleable non-fused ring backbones and dipodal phosphonic acid anchoring groups. The efficacy of configurational isomerism in modulating the photoelectronic properties and switching molecular orientation of PAs atop electrodes results in distinct substrate surface energy and electronic characteristics. The NFR-DPA with linear (C2h symmetry) and brominated backbone exhibits favorable face-on orientation and enhanced work function modification capability compared to its angular (C2v symmetry) and non-brominated counterparts. This makes it versatile HELs in mitigating interfacial resistance for energy barrier-free hole collection, and affording optimal active layer morphology, which results in an impressive efficiency of 19.11 % with a low voltage loss of 0.52 V for binary OSC devices and an excellent efficiency of 19.66 % for ternary OSC devices. This study presents a new dimension to design PA-based HELs for high-performance OSCs.